1995
DOI: 10.4098/at.arch.95-35
|View full text |Cite
|
Sign up to set email alerts
|

The trophic ecology of wolves and their predatory role in ungulate communities of forest ecosystems in Europe

Abstract: H. 1995. The trophic ecology of wolves and their predatory role in ungulate communities of forest ecosystems in Europe. Acta Theriologica 40: 335-386.Predation by wolves Canis lupus Linnaeus, 1758 in ungulate communities in Europe, with special reference to the multi-species system o f Białowieża Primeval Forest (Poland/Belarus), was assessed on the basis results of original research and literature. In historical times (post-glacial period), the geographical range of the w olf and most ungulate species in Euro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
126
0
12

Year Published

1997
1997
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 146 publications
(153 citation statements)
references
References 69 publications
(102 reference statements)
15
126
0
12
Order By: Relevance
“…Moose is the only wild ungulate in the study area (Helle et al 1997), and we hypothesized moose to be the major food source for the wolves in accordance with the findings of the majority of wolf diet studies, revealing that ungulates are the primary prey of wolves (eg Okarma 1995). As recommended by Ciucci et al (1996) we used more than one scat-analysis method, since comparison of results and interpretation of possible discrepancies help to avoid misleading conclusion by relying on a single method.…”
Section: Introductionsupporting
confidence: 81%
See 1 more Smart Citation
“…Moose is the only wild ungulate in the study area (Helle et al 1997), and we hypothesized moose to be the major food source for the wolves in accordance with the findings of the majority of wolf diet studies, revealing that ungulates are the primary prey of wolves (eg Okarma 1995). As recommended by Ciucci et al (1996) we used more than one scat-analysis method, since comparison of results and interpretation of possible discrepancies help to avoid misleading conclusion by relying on a single method.…”
Section: Introductionsupporting
confidence: 81%
“…Wolf diet studies conducted in Europe reveal that wolves Canis lupus often consume a wide spectrum of different prey species, but the major food source is wild ungulates (eg Okarma 1995, Olsson et al 1997. In our study area the dependence of wolves on ungulates was also clearly demonstrated, as moose was found to constitute far the most important food source in both summer and winter.…”
Section: Discussionsupporting
confidence: 51%
“…In contrast, red deer was generally positively selected in central-eastern Europe (Okarma 1995;Jędrzejewski et al 2000;Andersone and Ozolins 2004;Nowak et al 2005) and in the western Alps (Gazzola et al 2005), on the contrary roe deer was selected in fewer locations of Sweden (Olsson et al 1997), Saxony (Ansorge et al 2006), Russia and Belarus (Okarma 1995). Apart from Italy, wild boar was selected as secondary prey in the Bieszczady Mountains, Poland, during winter (Smietana and Klimek 1993;Gula 2004), in two locations of central Russia and Caucasus (Okarma 1995), and as main prey only in Estonia (Valdmann et al 1998).…”
Section: Prey Selectionmentioning
confidence: 86%
“…For instance, in the forests of Europe, up to five coexisting species of ungulates are subject to predation by (most typically) three large carnivores (eg Okarma 1995, to say nothing of the temperate forests in the Russian Far East (eg Sikhote-Alin Reserve), where seven large carnivores coexist with seven species of ungulates (Rakov 1979). A diverse spectrum of potential prey most likely affects both functional and numerical responses by predators, and -in consequence -the total predation rates.…”
Section: Introductionmentioning
confidence: 99%